Dimensions of the Shekhinah: The Meaning of the Shiur Qomah in Jewish Mysticism, Liturgy, and Rabbinic Thought - Sweeney, Marvin A. 1953- (2013)
The article discusses a Jewish mystical text that paradoxically takes up the measurements of the body of G-d in the context of a tradition that forbids corporeal, finite, or tangible depiction of the Deity. Consequently, scholars have been at a loss concerning its interpretation. Many resort to invective, labeling the work “a monstrosity” or “a malignant growth on the body of Judaism.” But others note its metaphorical or midrashic character, insofar as it appears to draw out the meaning of biblical texts that project a sense of G-d’s corporeal presence, and its gargantuan physical dimensions for the body of G-d that are beyond normal human comprehension. Three major aspects of the Shiur Qomah are considered: its relation to biblical texts that appear to describe G-d in physical terms; the incomprehensibility of the measurements given; and its liturgical character, with the descriptions of G-d’s body interspersed among elements of prayer and benediction that point to some form of heavenly worship. The paper concludes that the liturgical dimension is key: the readers are confronted with G-d’s unimaginable size in the context of a heavenly but recognizably Jewish service and thereby prompted to consider before whom they pray.